A compreensão de democracia no pensamento de Charles Taylor - Cleison Daniel Costa (2021)
The main aim of this work is to present the notion of democracy in the thought of the Canadian philosopher Charles Taylor. To do so, we start from the author’s critique of what we call liberal ‘atomist-procedural’ model of comprehension of democracy and we try to articulate an alternative model of comprehension that we call ‘liberal-republican’, which is considered by the philosopher as more receptive to freedom, pluralism and to the promotion of the common good. With this goal in mind, we first present Taylor’s analysis of the atomist anthropology that, so he understands, underlies most of hegemonic liberal theories in the West, an anthropology that the author links in its origins to the modern epistemological tradition at the base of a naturalistic perspective of science. To these atomist images of the human being and naturalistic of science, the philosopher opposes a conception of human agents as self-interpreting language animals that are situated in their time and relationships, as well as a comprehension of the social-political theory as a modality of self-understanding of the collective identity that focuses, essentially, on what is meaningful (conceptions of the good) to these agents. After this propaedeutic task, we dedicate ourselves to properly present Taylor’s interpretation of the ‘atomist-procedural’ liberalism and its weaknesses, as well as his comprehension of a different form of conceiving the democratic sociability that emerges from the author’s combination of variants of the theoretical languages of liberalism and republicanism. Having met this main objective, we propose as a closing point, to analyze elements of Brazilian political culture in dialogue with Taylor’s comprehension of democracy and of the political in general in order to clarify, to some extent, the democratic and undemocratic aspects of this culture. For this second task, we draw on interpreters of Brazilian social reality from different fields.